Answer:
-20 < 4 - 2x (subtract 4 from both sides)
-24 < -2x (divide each side by -2)
12> x (when you divide by a negative number, the inequality flips)
x< 12 ( I always put it so x is first)
so the answer is C
Answer:
f(x) + g(x) = x + 20
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
<u>Algebra I</u>
- Terms/Coefficients
- Functions
- Function Notation
Step-by-step explanation:
<u>Step 1: Define</u>
f(x) = 6x - 4
g(x) = -5x + 24
<u>Step 2: Find f(x) + g(x)</u>
- Substitute in functions: f(x) + g(x) = 6x - 4 + (-5x + 24)
- Combine like terms (x): f(x) + g(x) = x - 4 + 24
- Combine like terms: f(x) + g(x) = x + 20
Answer:
Solution given:
Since the given triangle is isosceles and right angled triangle
perpendicular [p]=base[b]=x
hypotenuse [h]=6
we have
by using Pythagoras law
p²+b²=h²
x²+x²=6²
2x²=36
x²=36/2
x²=18
x=
<u>x</u>=
588, (16-4/2)= 14
(14) square 2= 196
196•3= 588
:3